2005
DOI: 10.1111/j.1440-1746.2005.04070.x
|View full text |Cite
|
Sign up to set email alerts
|

Community‐based epidemiology of hepatitis B virus infection in West Bengal, India: Prevalence of hepatitis B e antigen‐negative infection and associated viral variants

Abstract: This first general population-based epidemiological study of HBV infection from India suggests that HBV acquisition starts in early childhood and peaks in adulthood. Most infections in the community are e-negative and inactive. The point prevalence of PC stop codon and BCP mutants is low in this primarily inactive and asymptomatic HBV-infected population sample in eastern India.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
38
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 36 publications
8
38
2
Order By: Relevance
“…7 Studies have attributed 20-80% of all new hepatitis B infections to unsafe injections, and have also implicated unsafe injections as a major mode of transmission of hepatitis C. 8 Other studies have highlighted the various risk factors for HBV infection like being older than 20 years of age, poverty, a low level of education, use of reusable glass syringes, being shaved by a community barber, and being born at home. 9 A study conducted on Armed Forces population has found highly significant association of HBV positivity with having indulged in sex with CSWs and taking injections in civil set up. 4 …”
Section: Methodsmentioning
confidence: 99%
“…7 Studies have attributed 20-80% of all new hepatitis B infections to unsafe injections, and have also implicated unsafe injections as a major mode of transmission of hepatitis C. 8 Other studies have highlighted the various risk factors for HBV infection like being older than 20 years of age, poverty, a low level of education, use of reusable glass syringes, being shaved by a community barber, and being born at home. 9 A study conducted on Armed Forces population has found highly significant association of HBV positivity with having indulged in sex with CSWs and taking injections in civil set up. 4 …”
Section: Methodsmentioning
confidence: 99%
“…[7] Five percent of our patients were HBsAg positive, which is little higher than the value reported from the general population (2.97%) of Eastern India. [8] High seroprevalence of these infections may be due to lack of anti-HCV screening of blood products in the blood banks in Government and private sector, proper screening in the blood banks using Third and Fourth generation ELISA test is not done correctly or may be the kits labelled as ELISA are at fault. Professional donors are also on the increase than voluntary donors.…”
Section: Discussionmentioning
confidence: 99%
“…According to the WHO report on prevention of HBV in India, 10 HBsAg prevalence among general population ranges from 0.1% to 11.7%, being between 2% and 8% in most studies. [15][16][17][18][19][20][21][22][23][24][25] In the first large general population-based epidemiological study of HBV infection from India, Chowdhury et al 26 assessed the prevalence of serological markers of HBV infection in 19 villages in Birbhum district of West Bengal in Eastern India. Of the 7653 individuals who were included in the study, 227 (2.9%) tested positive for hepatitis B surface antigen (HBsAg), of whom 204 (90%) were HBeAg-negative and hepatitis B e antibody (anti-HBe)-positive, and 78% had normal alanine aminotransferase levels.…”
Section: Population Studiesmentioning
confidence: 99%